على جودة خدمة التعليم العالي في ظل جائحة كورونا من وجهة نظر أساتذة كلية العلوم الاقتصادية لجامعة سوق أهراسmoodleأثر أرضية - روميسة قادري; شيماء هراقمي (My University, 2021)
The study aimed at evaluating the impact of digital education on the quality of service in the higher level of Mohammed Sharif Musadia University in Souk Ahras by education sector provided at the studying the impact of the model floor from the viewpoint of the professors of the Faculty of Economic Sciences at the university and this was done by relying on the descriptive analytical ch, and the form was adopted as a tool to collect Data from the study population The study approashowed the following results: • There is an effect of the quality of the model floor for Mohammed Sharif University, helping to ion service, achieve the quality of higher educat • Through the results of the descriptive statistics of the study sample, it was found that the sample members agreed on the degree often on the level of organization of the "Moodle" floor, due to the ous interaction with the floor. nature of their work that requires continu • Through the results of the descriptive analysis, it was found that the sample members agreed to Ease of handling the floor) due to the -design –choose sometimes on the level of quality (content e's computer technology engineers.inefficiency of the colleg ................................................ هدفت الدراسة إلى تقييم تأثير التعليم الرقمي على جودة الخدمة في قطاع التعليم العالي المقدمة على مستوى جامعة محمد الشريف مساعدية بسوق أهراس من خلال دراسة تأثير أرضية مودل من وجهة نظر أساتذة كلية العلوم الاقتصادية بالجامعة وتم ذلك بالاعتماد على المنهج الوصفي التحليلي، وتم اعتماد الاستمارة كأداة لجمع البيانات من مجتمع الدراسة وقد أظهرت الدراسة النتائج التالية: • وجود تأثير لجودة أرضية مودل لجامعة محمد الشريف مساعدية في تحقيق جودة خدمة التعليم العالي، • من خلال نتائج الإحصاء الوصفي لعينة الدراسة تبين أن أفراد العينة اتفقوا على الدرجة غالبا على مستوى تنظيم أرضية " Moodle " وذلك يعود إلى طبيعة عملهم التي تتطلب التفاعل المستمر مع الأرضية. • من خلال نتائج التحليل الوصفي تبين أن أفراد العينة اتفقوا على الاختيار أحيانا على مستوى جودة )المحتوى-التصميم-سهولة التعامل مع الأرضية( وذلك يعود إلى عدم كفاءة مهندسي الإعلام الآلي بالكلية.